Definition of cortical bone involvement in the staging of newly diagnosed pediatric Hodgkin lymphoma: A report from the International Working Group on Staging Evaluation and Response Criteria Harmonization (SEARCH). Issue 4 (22nd December 2019) - Lewis, Jocelyn; McCarten, Kathleen; Kurch, Lars; Flerlage, Jamie E.; Kaste, Sue C.; Kluge, Regine; Stoevesandt, Dietrich; Voss, Stephan D.; Kelly, Kara M.; Mauz‐Körholz, Christine; Drachtman, Richard A.; Metzger, Monika L.
Abstract: Background: The International Working Group on Staging Evaluation and Response Criteria Harmonization (SEARCH) seeks to provide a universally acceptable definition of cortical bone involvement in the staging of newly diagnosed pediatric Hodgkin lymphoma. Procedure: A comprehensive literature search was performed using PubMed and Google Scholar with the search terms "Hodgkin lymphoma, " "osseous lesions, " "bony involvement, " and "pediatric." Publications reviewed included case reports, retrospective analyses, and literature reviews. Each was evaluated for study design, number of participants, median age and age range at diagnosis, percentage of pediatric patients, criteria of interest definition, diagnostic tools, study objectives, and level of evidence. The final definition was based on the available data and consensus of the SEARCH working group. Results: Twenty‐five papers specifically addressing cortical bone involvement in Hodgkin lymphoma met the inclusion criteria. Eighteen papers were case reports with literature reviews; the remainder were observational cohort studies. Of these, 14 included pediatric patients (aged 0‐21 years). The criteria for cortical bone involvement were not clearly defined in any paper, often varied within a study, and were inconsistent between publications. Conclusions: The SEARCH group for Childhood, Adolescent, and Young Adult Hodgkin Lymphoma (CAYAHL) proposes the following criteria as defining cortical bone involvement: any cortical bone biopsy‐proven lesion; a positive bony window lesion on computer tomography (CT), with an FDG‐PET positive correlate in a patient with biopsy‐proven Hodgkin lymphoma,  if there is no other typical skeletal pathology; auspicious skeletal lesions on FDG‐PET or magnetic resonance imaging should be confirmed by CT or Tc‐99m scan to distinguish cortical lesions from bone marrow involvement. Nodal masses that extend into bone with bony destruction are considered extranodal extension or "E" lesions and do not represent metastatic or stage IV disease.